Entrepreneurial Government Attitude Towards The Performance of Local Government Officials - Agus Supandi Soegoto; Ritson Eras Kadisi (Faculty of Economic and Business, 2017)
Public demand for the implementation of good governance in the public sector for several years has been increasing because the performance of public services does not seem to meet public expectations. The purpose of this study is to determine the influence of entrepreneurial mental attitude on the performance of the government apparatus in the district of Sitaro Islands. The analytical method used is associative and relies on multiple linear regression. The results show that both simultaneously and partially, entrepreneurial government mental attitudes including innovator, brave and creative attitudes, creating value and recognizing opportunities, communication skills, human mobility, and resource have a positive and significant impact on the performance of government officials. The results also show the attitude of innovators has the lowest variable value which means that the leaders should enhance the attitude of Mental Entrepreneurial by improving the employees’ attitude of innovators, either through leadership training, entrepreneurship, or education quality improvement, therefore the performance of the officials may be enhanced.DOI: 10.15408/etk.v16i2.4968